Multi-Function Press Machine Pressing, Angle Bending, And Radius Bending - Muhammad umar, Umar Umar; Hanif, Faizin Muhammad; Fernando, Wahyu Wahyu; Hasibuan, Fardin Fardin (Universitas Riau Kepulauan, 2025)
The multifunctional press machine is an innovation designed to support metal fabrication processes with three main capabilities: pressing, angle bending, and radius bending. This machine can be used for steel plates with a thickness of 15 mm and a width of up to 800 mm, equipped with a hydraulic system to produce precise and stable pressure. The design process includes the design of main components, material selection, and performance testing to ensure optimal results. This machine aims to improve production efficiency, reduce waste, and produce high-quality products that meet the needs of education and industry, particularly at the University of Riau Kepulauan. Testing showed that the machine is capable of producing angle and radius formations with high accuracy. Its applications cover the automotive, manufacturing, and construction sectors, making it a multifunctional tool relevant for education, research, and small to medium-scale production.